STUDI KORELASIONAL ANTARA HUBUNGAN TEMAN SEBAYA DAN MOTIVASI BELAJAR SISWA KELAS V SD DI KELURAHAN MENTENG ATAS - Nabilah, Salsa; Imaningtyas; Anggi Citra Apriliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the relationship between peer relationships and learning motivation. The subjects of this research were all fifth-grade students at SDN Menteng Atas 01, SDN Menteng Atas 05, and SDN Menteng Atas 14, totaling 210 students. The research was conducted from March to June 2025. A quantitative correlational method was used to analyze the extent of the relationship between the two variables, whether the relationship is positive, negative, or nonexistent. Prerequisite tests indicated that the data were normally distributed, homogeneous, and linear. The results of the correlation test showed a Pearson Correlation value of 0.262 (indicating a weak correlation) with a p-value of < 0.001 (p < 0.05). Based on these findings, it can be concluded that there is a positive and significant relationship between peer relationships and the learning motivation of fifth-grade students in Kelurahan Menteng Atas.